REKONSTRUKSI ARSIP DI DINAS PENDIDIKAN, PEMUDA, DAN OLAHRAGA DAERAH ISTIMEWA YOGYAKARTA - , PULIH HATI HAREFA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final assignment report discuss about the record implementation reconstruction phase that it was done in Dinas Pendidikan, Pemuda, dan Olahraga DIY. Record reconstruction phase include record sorting, record classification, record in making chart, record description, description card maneuver, bundle maneuver, record envelopment, entering the record in the box, giving label to the box, and record ordering to the shelf in the record center. The institution has high level development in record, but it is not followed with good management. There is no an archivist in the institution and it becomes main obstacle in the record management. In addition, the institution do not have budget especially in record. This final assignment report aimed to explain about how the record implementation reconstruction phase that it was done in Dinas Pendidikan, Pemuda, dan Olahraga DIY, and obstacle that the institution faced in managing the record with inactive dynamic. There are some methods that the institution used to collect data